2021
DOI: 10.3390/ma14081980
|View full text |Cite
|
Sign up to set email alerts
|

Is Dental Amalgam a Higher Risk Factor rather than Resin-Based Restorations for Systemic Conditions? A Systematic Review

Abstract: Objective: The aim of this study was to confirm the hypothesis that patients with one or more amalgam restorations have an increased risk for systemic diseases rather than patients with resin-based restorations. Data: The data search produced an initial 3568 total number of records. All titles and abstract were reviewed by five independent examiners, and only 36 records were selected for full text in depth examination. Out of these, only nine publications matched the inclusion criteria and were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
6
0
6
Order By: Relevance
“…Common packaging materials include liposomes, nanoparticles, and microcapsules [ 110 ]. Additionally, according to Gallusi et al [ 111 ], dental amalgam was not as toxic as expected, and human clinical studies have shown no increased risk for systemic diseases or conditions compared with composite restorations. Therefore, a systemic route is applicable for the delivery of antioxidants.…”
Section: Antioxidants Used In Dental Proceduresmentioning
confidence: 91%
“…Common packaging materials include liposomes, nanoparticles, and microcapsules [ 110 ]. Additionally, according to Gallusi et al [ 111 ], dental amalgam was not as toxic as expected, and human clinical studies have shown no increased risk for systemic diseases or conditions compared with composite restorations. Therefore, a systemic route is applicable for the delivery of antioxidants.…”
Section: Antioxidants Used In Dental Proceduresmentioning
confidence: 91%
“…Rtęć kumuluje się i ulega addycji przez wiele tysięcy lat, a najwyższe stężenie osiąga w organizmach na końcu łańcucha pokarmowego, jakimi są ludzie i ryby drapieżne [2,3]. Badania donoszą, że rtęć powoduje wiele zaburzeń fizjologicznych i niesie za sobą niekorzystne skutki medyczne, rozpoczynając od bioakumulacji w ośrodkowym układzie nerwowym, nerkach i wątrobie, przyczyniając się do uszkodzenia nerek, immunotoksyczności, genotoksyczności, spadku płodności oraz zmiany funkcjonowania osi endokrynologicznych [4,5,7,[16][17][18][19][20]. Amalgamaty stosowane do wypełniania ubytków w stomatologii stanowią główne i przewlekłe źródło narażenia pacjentów na nieorganiczną rtęć [6,14].…”
Section: Wprowadzenieunclassified
“…Jego właściwości przyczyniają się do tego, że chętnie jest wykorzystywany przez stomatologów do odbudowy zębów bocznych. Wypełnienie amalgamatowe zawiera około 50% rtęci oraz mieszaninę innych metali takich jak srebro, cyna, miedź i inne [1][2][3][4][6][7][8][9][10][11]13,14,[17][18][19][20][21][22][23][24][25][26]. Amalgamaty niskomiedziowe wykazują mniejszą rozpuszczalność w kwasach niż amalgamaty wysokomiedziowe oraz niższą szybkość korozji, co sprawia że emisja par rtęci z wypełnień jest znacząco niższa [18].…”
Section: Amalgamat Dentystycznyunclassified
See 1 more Smart Citation
“…Within the last 20 years, clinical studies evaluated possible associations of dental amalgam with neurological and autoimmune diseases and showed controversial results [ 67 , 68 , 69 , 70 , 71 ]. According to the systematic review published by Gallusi et al in 2021, amalgam restorations are not associated with an increased risk of any systemic disease [ 72 ]. Nevertheless, the issue of the potential toxicity of mercury released from dental amalgams is a matter of debate in the scientific literature [ 73 ].…”
Section: Clinical Manifestations Of Adverse Effects Associated With D...mentioning
confidence: 99%